CARDIOVASCULAR DISEASES OF THE LENINGRAD SIEGE SURVIVORS - NEW RISK FACTORS RESEARCH - M. P. Rotar; E. V. Moguchaya; E. P. Kolesova; M. A. Boyarinova; A. M. Erina; E. A. Dudorova; M. A. Ilyina; V. N. Solntsev; A. O. Konradi (Российский кардиологический журнал, 2014)
Aim. To assess the influence of starvation on the prevalence of cardiovascular risk factors and diseases in survivors of Leningrad Siege, depending on the starvation occurrence. Material and methods. Leningrad Siege survivors from Primorsky district of Saint-Petersburg were invited and examined during December 2009 to January 2012. All participants were interviewed by a questionnaire regarding lifestyle, risk factors, cardiovascular disease, comorbidities and medication. Blood pressure (BP) measurements and anthropometry (weight, height, waist and neck circumference) were performed according to standard procedures. Fasting serum lipids and plasma glucose were measured on Hitachi-902. Echocardiography (Vivid 7) and electrocardiography (MAC1200ST) were performed. 305 survivors of Leningrad Siege (224 (73%) females and 81 (27%) males) were examined, the mean age was 70,5 yrs. In the control group were 46 patients with similar gender and age pattern — 31 (67%) females and 15 (33%) males, mean age was 71,3 years. All people were divided in two groups: who was born during the Leningrad Siege (45 (14,7%)) and before the Leningrad Siege (260 (85,3%) subjects) in the period from 1928 to 1941.Results. Siege survivors had lower anthropometric indexes but higher HDL level comparing with control group. There were no significant differences in the prevalence of cardiovascular disease in 2 groups: only chronic CHD was more often (48,9% vs 33,3%, р=0,04) and prevalence of atrial fibrillation was slightly lower (17% vs 8.5%, p=0,05) in siege survivors comparing with the controls. Survivors who were undergone the starvation during childhood and adolescent period more often had hypertriglyceridemia comparing with subjects after intrauterine starvation. Diagnosis of myocardial infarction (16 (19,8%) vs 16 (7,2%), p=0,002) and AF (13 (16%) vs 12 (5,35%), respectively, p=0,02) were detected more often in men comparing with women. Males less often had hypercholesterolemia (39 (48,1%) vs 170 (75,8%), р<0,0001) and abdominal obesity (43 (53,0%) vs 162 (72,3%), р=0,001) than females.Conclusions. No significant influence of starvation during Leningrad Siege on cardiovascular risk factors and diseases was revealed. Delayed consequences of starvation appeared to be less important than other risk factors and heredity predisposition.